Improving Understanding in the Development of Teaching Modules in the Independent Curriculum through Training of Mathematics Teacher - Karim Karim; Taufiq Hidayanto; Kamaliyah Kamaliyah; Asdini Sari; Muhammad Rayhan Ramadhan; Muhammad Alif Anwar (Universitas Lambung Mangkurat, 2024)
In implementing the